Tout Fait Maison:: A Law Code Crafted by the Eighteenth Century Jewry of Metz - Herman, Shael (The review of rabbinic Judaism, 2018)
This inquiry examines Le Recueil des Loix, Coutumes, et Usages Observes par les Juifs de Metz. Evocative of the medieval German Sachsenspiegel, the volume’s detailed regulations supply a rich portrait of a Jewish community in Alsace-Lorraine during the turbulent final decades of the ancien regime. While France evolved during these decades from feudalism to democracy, the Jews transitioned from serfs main-mortables or royal chattels to citizenship. Ideals of the emerging French democracy were imprinted upon the Code Napoleon (1805), a distinctively anti-feudal, secular expression of French citizens’ newfound autonomy. In contrast, the Recueil originated in an act of will on the part of the Jews’ overlords. In accordance with royal orders, it was deposited in the records of the royal court at Metz in about 1742; royal judges and members of the bar consulted the Recueil in all manner of disputes involving Jewish litigants and Jewish law. The Recueil, as the handiwork of eighteenth century Alsatian Jews, was unique in engrafting Jewish law and ethics upon French law of the ancien regime.